Some topological properties and asymptotic behavior of the higher eigencurves for the $p$-laplacian operator with weight - Moussaoui Mimoun; Ahmed Dakkak; Omar Chakrone (Boletim da Sociedade Paranaense de Matemática, 2022)
In this papers we prove the existence of the higher eigencurves for the $p$-laplacian operator with weight, we gives its variational formulation, we study its monotonicity, continuity properties and its asymptotic behavior.